2001
DOI: 10.4269/ajtmh.2001.65.759
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B virus infection and related risk factors in a rural community of Mexico.

Abstract: Abstract.A cross-sectional survey of the seroprevalence of hepatitis B virus (HBV) markers among healthy people was conducted in San Juanito, a rural community in the northern state of Chihuahua, Mexico. The overall prevalence in 970 people was 6.6% for antibody to hepatitis B core antigen. There was an age effect on the prevalence of HBV infection, and a gradual increase in prevalence was observed in patients up to the age of 40 years. Those subjects with a history of dental procedures had a 2-fold higher ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
7
26
0
1
Order By: Relevance
“…This has also been observed by others (Dominguez et al 2000, Cisneros-Castolo et al 2001, Gandolfo et al 2003. More, older adolescents had 3.6 fold (95% CI: 1.6-7.9) more chance to be exposed to HBV than those younger, suggesting changes in the lifestyle linked with risk behaviors for hepatitis B transmission.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This has also been observed by others (Dominguez et al 2000, Cisneros-Castolo et al 2001, Gandolfo et al 2003. More, older adolescents had 3.6 fold (95% CI: 1.6-7.9) more chance to be exposed to HBV than those younger, suggesting changes in the lifestyle linked with risk behaviors for hepatitis B transmission.…”
Section: Discussionsupporting
confidence: 80%
“…This is higher when compared with data in adolescents and young adults from developed countries where hepatitis B vaccination programs were fully implemented such as Greece (2.5%) (Gogos et al 2003), Italy (0.9%) (Bonanni et al 2003), Spain (0.9%) (Salleras et al 2005), and the United States (1%) (McQuillan et al 1989). However, regarding individuals from developing regions where HBV vaccination programs were partially or not implemented, this prevalence was similar to that observed in Mexico (5%) (Cisneros-Castolo et al 2001) and Bolivia (6.9%) (Gandolfo et al 2003). In Brazil, Clemens et al (2000) reported a rate of 5.2% in adolescents of four regions, ranging from 2.5% in those with better socioeconomic conditions to 9% in lowincome individuals.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, this prevalence is lower than that of Greece (2.5%) 24 and of developing regions, where HBV vaccination programs are only partially implemented or not implemented at all, such as Mexico (5%) 25 , Bolivia (6.9%) 26 and central Brazil (5.9%) 27 .…”
Section: Ethical Considerationsmentioning
confidence: 59%
“…Cultural or behavioural factors which have been described in some communities, e.g. injections using unsterilized needles [27], sharing of personal and household articles [28], dental procedures and tattoos in unsafe circumstances [29] were enquired about directly or indirectly, but their effects could not be shown in this study.…”
Section: Discussionmentioning
confidence: 77%